911. Assessment of Representativeness of IPD Surveillance Conducted by the National Microbiology Laboratory of Canada. (31st December 2020) - Nepal, Rajeev M; Dion, Stephane B; Grajales, Ana Gabriela; Major, Maria; Cane, Alejandro; Vojicic, Jelena
Abstract: Background: Understanding the evolving epidemiology of Streptococcus pneumoniae serotypes is important for assessing the current and potential future immunization programs. In Canada, Invasive pneumococcal disease (IPD) is mandatory reportable to provincial/territorial public health. Provinces and territories voluntarily submit annual IPD data to the Canadian Notifiable Disease Surveillance System (CNDSS), which publishes information on IPD cases and incidence rates, however serotype data are not available. Provinces/territories also voluntarily submit IPD isolates to the National Microbiology laboratory (NML) for serotyping; provinces that conduct their own serotyping submit this information. The NML produces comprehensive IPD surveillance reports including serotype distribution; due to lack of population denominator, no incidence rates are available. The two surveillance programs are not linked. The objective of the study is to assess the representativeness of the NML surveillance as compared to the CNDSS and provincial reportable diseases databases. Methods: Over the study time period (2010-2017), we compared annual IPD case counts between the NML and CNDSS reports. Due to the difference in age grouping between CNDSS and NML, comparison was limited to these groups: all age, < 5, 5-14 and > 15 years. In addition, the IPD counts from NML were compared to data from four largest provinces. Results: For < 5 group, NML reported 91% of CNDSS case count whereas for 5-14 and > 15 years of age, it was 81% and 79%, respectively. Compared to the corresponding provincial databases, NML reported 91%, 97%, and 93% case counts for Ontario, British Columbia, and Alberta, respectively, while it was only 47% for Quebec. Further analysis revealed that the discrepancy in Quebec is the result of under-representation of >5 populations. Figure 1: Comparison of age stratified IPD case counts between CNDSS and NML Figure 2. Comparison of all age IPD case counts between NML and provincial databases Conclusion: IPD surveillance conducted by NML has been instrumental to gain insight into the evolving epidemiology of S. pneumoniae serotypes in Canada. Comparisons of IPD counts from NML surveillance reports with reportable disease databases revealed different levels of concordance across provinces and age groups. The limitations of NML surveillance including incomplete or inconsistent reporting should be taken into consideration when interpreting the data. Disclosures: Rajeev M. Nepal, PhD, Pfizer (Employee) Stephane B. Dion, PhD, Pfizer (Employee) Ana Gabriela Grajales, MD, Pfizer (Employee) Maria Major, B.Sc., MPH, Pfizer (Employee) Alejandro Cane, MD, Pfizer (Employee) Jelena Vojicic, MD, Pfizer (Employee)